Cerebellum Dysfunction in Patients With PRRT2-Related Paroxysmal Dyskinesia. (8th March 2022) - Ekmen, Asya; Meneret, Aurelie; Valabregue, Romain; Beranger, Benoit; Worbe, Yulia; Lamy, Jean-Charles; Mehdi, Sofien; Herve, Anais; Adanyeguh, Isaac; Temiz, Gizem; Damier, Philippe; Gras, Domitille; et al.
Abstract : Background and Objectives: The main culprit gene for paroxysmal kinesigenic dyskinesia, characterized by brief and recurrent attacks of involuntary movements, is PRRT2 . The location of the primary dysfunction associated with paroxysmal dyskinesia remains a matter of debate and may vary depending on the etiology. While striatal dysfunction has often been implicated in these patients, evidence from preclinical models indicates that the cerebellum could also play a role. We aimed to investigate the role of the cerebellum in the pathogenesis of PRRT2 -related dyskinesia in humans. Methods: We enrolled 22 consecutive right-handed patients with paroxysmal kinesigenic dyskinesia with a pathogenic variant of PRRT2 and their matched controls. Participants underwent a multimodal neuroimaging protocol. We recorded anatomic and diffusion-weighted MRI, as well as resting-state fMRI, during which we tested the aftereffects of sham and repetitive transcranial magnetic stimulation applied to the cerebellum on endogenous brain activity. We quantified the structural integrity of gray matter using voxel-based morphometry, the structural integrity of white matter using fixel-based analysis, and the strength and direction of functional cerebellar connections using spectral dynamic causal modeling. Results: Patients with PRRT2 had decreased gray matter volume in the cerebellar lobule VI and in the medial prefrontal cortex, microstructural alterations of white matter in the cerebellum and along the tracts connecting the cerebellum to the striatum and the cortical motor areas, and dysfunction of cerebellar motor pathways to the striatum and the cortical motor areas, as well as abnormal communication between the associative cerebellum (Crus I) and the medial prefrontal cortex. Cerebellar stimulation modulated communication within the motor and associative cerebellar networks and tended to restore this communication to the level observed in healthy controls. Discussion: Patients with PRRT2 -related dyskinesia have converging structural alterations of the motor cerebellum and related pathways with a dysfunction of cerebellar output toward the cerebello-thalamo-striato-cortical network. We hypothesize that abnormal cerebellar output is the primary dysfunction in patients with a PRRT2 pathogenic variant, resulting in striatal dysregulation and paroxysmal dyskinesia. More broadly, striatal dysfunction in paroxysmal dyskinesia might be secondary to aberrant cerebellar output transmitted by thalamic relays in certain disorders. Trial Registration Information: ClinicalTrials.gov identifier: NCT03481491.